Protection and risk for different school stress trajectories - Correia-Zanini, Marta Regina Gonçalves; Loureiro, Sonia Regina; Marturano, Edna Maria (Paidéia (Ribeirão Preto), 2020)
The study of chronic stress, potentially harmful to development, resents the focus of research on modal trends, not discriminating individual trajectories of chronicity. This study aimed to associate groups differentiated by the trajectory of stress, in children from the 1st to the 3rd year of Elementary School - Without Stress, Acute Stress and Chronic Stress, to the variables of protection or risk of the child and the school itself. One hundred and eleven students (56 boys) participated in the Child Stress Scale, Provinha Brasil, School Stressors Inventory and Social Skills Rating System - Teachers. Early childhood education, the Basic Education Index and the location of the school were considered. Comparison and prediction analyses were performed. Results indicated worse performance and greater perception of stressors in the group with chronic stress. Externalizing behavior, performance stressors and less permanence in Early Childhood Education contribute to chronicity. The focus on trajectories highlighted the vulnerability of chronically stressed children.